Invisible hand behind the corporate governance practices in Malaysia - Htay, Sheila Nu Nu (s.n, 2012)
This issues of corporate governance became very popular in the corporate world in UK, USA and Europe during the last two decades. In Malaysia, Malaysia Code on Corporate Governance was introduced in 1998 and eventually; it has been amended in 2000 and 2007. However, some of the finding on corporate governance in Malaysia are not in line with the recommendation of the Code. Thus, this study examines the possible reasons that hinder current corporate governance system less effective in Malaysia. The main reasons for this problem are due to nature of ownership structure, political and culture background of Malaysia and the adoption of unsuitable foreign corporate governance template. The finding of this research will be useful for the regulators to develop future rules and regulations and implement them accordingly